How to catch a star - Jeffers, Oliver (New York : Philomel Books, 2004)
Eager to have a star of his own, a boy devises imaginative ways of catching one.
Booklist.
Horn Book.
School Library Journal.
2.7
K-3
Keywords: Stars -- Juvenile fiction; Stars -- Fiction; Stars -- Fiction